2003
DOI: 10.1002/jbm.a.10037
|View full text |Cite
|
Sign up to set email alerts
|

A biodegradable electrical bioconductor made of polypyrrole nanoparticle/poly(D,L‐lactide) composite: A preliminary in vitro biostability study

Abstract: The electrical stability of a novel polypyrrole (PPy)/poly(D,L-lactide) (PDLLA) composite was studied in vitro and compared with that of PPy-coated polyester fabrics. Specimens were incubated in Ringer's solution at 37 degrees C for up to 8 weeks with or without the circulation of DC current under a constant 100 mV voltage. In situ current variation with incubation time was recorded. The AC volume electrical conductivity of the specimens before and after incubation in phosphate-buffered saline was recorded usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 15 publications
0
49
0
Order By: Relevance
“…Studies have found that fibroblasts attached and grew well on the PPy nanoparticle-PLA composites with an increased viability when stimulated at currents of 10 -50 mA. This material retained biocompatibility in vivo even after maintaining electroconductivity for long periods of time (15% of conductivity retained after 1000 h; Wang, Z. et al 2003Wang, Z. et al , 2004Wang, X. et al 2004). Similarly, PANI -chitosan nanocomposites and PANI -gelatin cross-linked composites have been explored to increase biocompatibility and enhance surface characteristics.…”
Section: Physical -Chemical Modificationsmentioning
confidence: 99%
“…Studies have found that fibroblasts attached and grew well on the PPy nanoparticle-PLA composites with an increased viability when stimulated at currents of 10 -50 mA. This material retained biocompatibility in vivo even after maintaining electroconductivity for long periods of time (15% of conductivity retained after 1000 h; Wang, Z. et al 2003Wang, Z. et al , 2004Wang, X. et al 2004). Similarly, PANI -chitosan nanocomposites and PANI -gelatin cross-linked composites have been explored to increase biocompatibility and enhance surface characteristics.…”
Section: Physical -Chemical Modificationsmentioning
confidence: 99%
“…But all faced the same issue, which is that PPy is regarded as non-degradable. Even though the biodegradation behaviour and in vivo biocompatibility of poly(D,Llactide) (PDLLA)-PPy composites (similar to the composites used in the present study) have been evaluated by Wang et al [46,47], with the conclusion that the tissue reaction was not affected by the presence of PPy, the challenge remains to keep a sufficient conductivity at the lowest possible PPy concentration [11]. In parallel, research is being carried out on the synthesis of PPy-based polymers that would be inherently conductive and fully biodegradable, the difficulty being to maintain a conductivity that allows electronic applications [48].…”
Section: (A) Development Of New Biodegradable Conducting Materialsmentioning
confidence: 99%
“…Due to the difficulty of biodegradable PPy-based copolymers to maintain enough conductivity for electrical applications, composites made of a biodegradable polymer matrix and PPy conducting nanoparticles become a highly interesting approach. Thus composites based on PDLLA [68,69], PDLLA/GA [69], PDLLA/CL [70], PLLA [71,72] and PCL [71,72] matrices and PPy nanoparticles have been developed. Addition of a small percentage of PPy nanoparticles had no effect on the in vivo degradation behaviour of the biodegradable materials [68,69] and consequently a low enough concentration of PPy nanoparticles should not give an inflammatory response when the composite degrades, and the remaining PPy nanoparticles should be later evacuated by the body, in a similar process as described for the implanted biodegradable stents made of biodegradable metals.…”
Section: Development Of Novel Biodegradable Polymes and Blends Based mentioning
confidence: 99%
“…Thus, resistivity of composite samples exhibited typical percolation behavior, with a threshold at a PPy content of approximately 3 wt % and the surface resistivity varied from 2 × 10 7 to 15 Ω/square when the wt % of PPy increased from 1 to 17. It is well known that PPy underwent dedoping and deprotonation under the synergic action of water and current [69], and hence the exposure of samples to a physiological environment can eventually decrease the electrical conductivity. Interestingly, the electrical stability under a physiological environment (Eagle's minimum essential medium) was significantly better in the PPy/PDLLA composite than in PPy-coated polyester fabrics (i.e., membranes having 5 wt % of PPy retained 80% and 42% of the initial conductivity in 100 and 400 h, respectively, compared to 5% and 0.1% for the PPy-coated polyester fabrics).…”
Section: Development Of Novel Biodegradable Polymes and Blends Based mentioning
confidence: 99%